2020
DOI: 10.1111/anae.15255
|View full text |Cite
|
Sign up to set email alerts
|

Conventional landmark palpation vs. preprocedural ultrasound for neuraxial analgesia and anaesthesia in obstetrics – a systematic review and meta‐analysis with trial sequential analyses

Abstract: The aim of this systematic review and meta-analysis was to examine the efficacy, time taken and the safety of neuraxial blockade performed for obstetric patients with the assistance of preprocedural ultrasound, in comparison with the landmark palpation method. The bibliographic databases Central, CINAHL, EMBASE, Global Health, MEDLINE, Scopus and Web of Science were searched from inception to 13 February 2020 for randomised controlled trials that included pregnant women having neuraxial procedures with preproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…The clinical significance of the improved first-pass success rate and reduced number of skin punctures required for the TEP in Gp-Usg of this study is not entirely clear as there are no comparable data in the literature. However, a recent systematic review and meta-analysis [ 29 ] comparing the landmark-based technique with a preprocedural ultrasound scan for neuraxial anesthesia in the obstetric population found that a preprocedural ultrasound significantly increased the first-pass success rate and reduced the incidence of complications including bloody tap or vascular cannulation, and postpartum headache and backache [ 29 ]. The Authors [ 29 ] hypothesized that the reduced skin punctures and needle redirections during the neuraxial block may decrease the potential for the development of micro-hematoma in the back and thus lower the incidence of postpartum backache.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of the improved first-pass success rate and reduced number of skin punctures required for the TEP in Gp-Usg of this study is not entirely clear as there are no comparable data in the literature. However, a recent systematic review and meta-analysis [ 29 ] comparing the landmark-based technique with a preprocedural ultrasound scan for neuraxial anesthesia in the obstetric population found that a preprocedural ultrasound significantly increased the first-pass success rate and reduced the incidence of complications including bloody tap or vascular cannulation, and postpartum headache and backache [ 29 ]. The Authors [ 29 ] hypothesized that the reduced skin punctures and needle redirections during the neuraxial block may decrease the potential for the development of micro-hematoma in the back and thus lower the incidence of postpartum backache.…”
Section: Discussionmentioning
confidence: 99%
“…Intubation and extubation were identified as aerosol generating procedures and high risk for the spread of Covid-19 leading to a preference for regional anaesthesia over GA where possible [7,8]. At the time of this case it was recommended to wear full PPE when conducting general anaesthesia and staff were issued with either an FFP3 mask, a JSP Force 8 or Force 10 mask (JSP, Minster Lovell, UK).…”
Section: Discussionmentioning
confidence: 99%
“…Between spinal curvature, possible spinal hardware, and baclofen pump incision scar tissue, the epidurals placed without image guidance had the potential to be technically challenging, so there is a theoretical benefit to using fluoroscopy, both in terms of total time and number of needle passes. Ultrasound imaging has been shown to be beneficial in parturients with anticipated difficult labor epidural placement 13 ; however, similar data are not available for children. A larger, prospective study would be required to determine any timing differences.…”
Section: Discussionmentioning
confidence: 99%